Intramedulary Epidermoid Cyst of the Dorsal Spine: A Case Report - Alam, Md. Shafiul; Farzana, Tayseer (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2017)
Spinal epidermoid cysts are cystic tumours lined by squamous epithelium. Unlike dermoid cysts, they do not contain skin appendages (hair follicles, sweat glands, sebaceous glands). They are usually extramedullary but rarely can be intramedullary. They may be congenital or acquired. Especially they are not associated with spinal dysraphism. Intramedullary epidermoid cysts of the spinal cord are rare tumours, only few cases having been reported in the literature. They comprise between 0.5% to 1% of all spinal tumours but account for up to 10% of intraspinal tumours in children. We report a case of 45 years-old female patient who presented with a 18 months history of progressive lower extremityweakness and spasticity. But her bowel/bladder function was normal. Magnetic resonance imaging of the thoracic spine revealed a 3 cm intramedullary mass at the T3-4 level. A T3 to T5 laminnectomy with complete removal of the intradural mass was performed. Intraoperative findings and final histopathological examination revealed an epidermoid cyst.Total excision of the tumor was performed. The patient showed progressive recovery.